Tau secretion and propagation: Perspectives for potential preventive interventions in Alzheimer's disease and other tauopathies - Annadurai, Narendran; De Sanctis, Juan B; Hajdúch, Marián; Das, Viswanath (Experimental neurology, 2021)
Alzheimer's disease (AD) is characterised by the accumulation of intracytoplasmic aggregates of tau protein, which are suggested to spread in a prion-like manner between interconnected brain regions. This spreading is mediated by the secretion and uptake of tau from the extracellular space or direct cell-to-cell transmission through cellular protrusions. The prion-like tau then converts the endogenous, normal tau into pathological forms, resulting in neurodegeneration. The endoplasmic reticulum/Golgi-independent tau secretion through unconventional secretory pathways involves delivering misfolded and aggregated tau to the plasma membrane and its release into the extracellular space by non-vesicular and vesicular mechanisms. Although cytoplasmic tau was thought to be released only from degenerating cells, studies now show that cells constitutively secrete tau at low levels under physiological conditions. The mechanisms of secretion of tau under physiological and pathological conditions remain unclear. Therefore, a better understanding of these pathways is essential for developing therapeutic approaches that can target prion-like tau forms to prevent neurodegeneration progression in AD. This review focuses on unconventional secretion pathways involved in the spread of tau pathology in AD and presents these pathways as prospective areas for future AD drug discovery and development.
Keywords: proteiny tau; Tau aggregation; Cell Communication; Brain; Prion-like protein; Neurodegenerative diseases; tauopatie; patologická konformace proteinů; Alzheimerova nemoc; Alzheimer Disease; tau Proteins; Animals; lidé; Humans; zvířata; mozek; Tauopathies; Extracellular tau; Tau propagation; Protein Aggregation, Pathological; Unconventional tau secretion; Alzheimer's disease; mezibuněčná komunikace